Climate Change Impacts on High-Altitude Ecosystems - Öztürk, Münir; Hakeem, Khalid Rehman; Faridah-Hanum, I.; Efe, Recep (Springer International Publishing : Imprint: Springer, 2015)
This comprehensive work provides insight into problems related to ecosystem fragmentation, health and well-being of high-altitude ecosystems, ecosystem services for food and medicine, and the issue of invasive alien species. This research has been collected by the world's most respected experts in climate change and ecology from Turkey, Pakistan, South America, Malaysia, Nepal, Kirgizistan, Kazakistan, Georgia, Russia, Macedonia, Indonesia, and North America. These experts discuss ecosystem health and productivity, climate change, threats to high-altitude ecosystems, soils, and other limiting environmental factors at high altitudes. The data presented here covers some of the most important mountain ranges in the world, including the Himalayas, Andes, Altai, Tien-Shan, and Caucasus. Climate Change Impacts on High-Altitude Ecosystems focuses on improving our understanding on the effects of climate change on biodiversity and provides insight to young researchers on these fragile ecosystems for their future evaluation.